Thermodynamic Analysis of Hydrogen Production Processes - Braga, L. B. [UNESP]; Tuna, C. E. [UNESP]; De Araujo, F. H.M. [UNESP]; Vane, L. F. [UNESP]; Pedroso, D. T. [UNESP]; Silveira, J. L. [UNESP] (Springer Nature, 2017)
In this chapter, thermodynamic studies are conducted for determining the energy efficiencies of each type of hydrogen production process. In the case of the steam reforming processes, a physicochemical analysis was previously conducted, which was based on the concepts of Gibbs free energy, equilibrium constant, and degree of advancement. In light of pressure and temperature conditions, the energy efficiency levels of such processes are determined. In the case of hydrogen production from renewable electrolytic processes, it was based on the electrolyzer’s efficiency and the average efficiencies of wind, photovoltaic, and hydroelectric power plants. In the case of algae, it was considered the energy contained in the hydrogen being produced and the energy consumption levels during the periods of growth, adaptation, and hydrogen production.
Keywords: Electrolytic processes; Energy efficiencies; Gibbs free energy; Physicochemical analysis; Plasma reforming; Steam reforming; Thermochemical reactions; Thermodynamic analysis; Thermodynamic efficiency